Cerebral perfusion after repair of congenital diaphragmatic hernia with common carotid artery occlusion after ECMO therapy - Henzler, Claudia; Zöllner, Frank G.; Weis, Meike; Zimmer, Fabian; Schönberg, Stefan; Zahn, Katrin; Schaible, Thomas; Neff, Wolfgang (In vivo, 2017)
Aim: To prospectively evaluate cerebral perfusion after repair of congenital diaphragmatic hernia (CDH) and right-common-carotid-artery (rCCA) occlusion after extracorporeal membrane oxygenation (ECMO) therapy. Patients and Methods: A total of 29 2-year-old-children with a history of CDH repair underwent cerebral magnetic resonance perfusion imaging. In 14 patients, the rCCA was occluded after ECMO therapy. Fifteen patients with CDH without ECMO served as controls. Regional cerebral-blood-flow (rCBF) was measured cortically and subcortically in both hemispheres and compared intra-individually and between both groups. Results: Patients with rCCA-occlusion showed intra-individual side differences between hemispheres, with significantly lower subcortical perfusion of the right hemisphere and reduced cortical perfusion. In one-third of patients with rCCA-occlusion, rCBF of the right-hemisphere was reduced by more than 20% when compared to the left hemisphere. Despite intra-individual side differences, mean rCBF in patients with rCCA occlusion was not reduced compared to controls. Conclusion: Beside intra-individual side differences, overall right hemisphere perfusion is sufficient after rCCA-occlusion due to collateral blood supply.
Gesehen am 18.06.2018